Fenomenologi Toxic Relationship dalam Komunikasi Interpersonal pada Mahasiswa Dewasa Muda - Syafdana, Nanda Nabila; Gumelar, Rangga Galura (Universitas Medan Area, 2024)
The relationship between partners is essentially related to gender equality, without the concept of domination in heterosexual relationships. However, many couples experience unhealthy and toxic relationships. Interpersonal communication in such relationships tends to be negative, creating feelings of self-restriction. This research aims to describe the phenomenon of toxic relationships in young adult interpersonal communication. The method used is qualitative descriptive with a phenomenological approach and constructivist paradigm. The research focuses on the young adult phase vulnerable to emotional instability, lack of independence, and immaturity that trigger toxic relationships. Toxic relationships can impact an individual's important interpersonal communication skills for the future. The study concludes that toxic relationships are common among young adult students, especially females. Ineffective communication in toxic relationships is caused by domination and loss of emotional control, making it difficult for subjects to express themselves freely. This transforms interpersonal communication, which should build trust, into a source of conflict and anxiety, even after separating from toxic partners.